Non-standard employment in Sweden - Per Skedinger (Research Institute of Industrial Economics (IFN), 2018)
In Sweden, as in many other countries, marginal groups tend to be overrepresented in non-standard employment. A decomposition of the employment rate of full-time workers on permanent contracts reveals that non-standard employment contributes to a substantially weaker labour market attachment for females and the foreign born than suggested by conventional employment figures alone. Our econometric analysis shows that the negative wage premia associated with fixed-term employment are considerably smaller in Sweden, both for natives and foreign born, than those that have been found for other countries. This may be due to a highly compressed wage structure and extensive coverage of collective bargaining in Sweden. On the whole, the type of fixed-term contract seems not to matter for the estimated wage premia.
Keywords: J21; J31; 330; Fixed-term employment; Part-time employment; Labour market attachment; Wage differentials